FTP Code : International code for application of fire test procedures, 2010 : (Resolution MSC. 307(88)). (OMI, 2012)
"The 2010 FTP Code, along with relevant SOLAS amendments to make it mandatory, was adopted, with an expected entry into force date of 1 July 2012. The 2010 FTP Code provides the international requirements for laboratory testing, type approval and fire test procedures for products referenced under SOLAS chapter II-2. It comprehensively revises and updates the current Code, adopted by the MSC in 1996. The 2010 FTP Code includes the following: test for non-combustibility; test for smoke and toxicity; test for "A", "B" and "F" class divisions; test for fire door control systems; test for surface flammability (surface materials and primary deck coverings); test for vertically supported textiles and films; test for upholstered furniture; test for bedding components; test for fire-restricting materials for high-speed craft; and test for fire-resisting divisions of high-speed craft. It also includes annexes on Products which may be installed without testing and/or approval and on Fire protection materials and required approval test methods."--Provided by publisher.